Swedish Plectida (Nematoda). Part 7. Setostephanolaimus tchesunovi sp. n. from the west coast of Sweden - Holovachov, Oleksandr (Zootaxa, 2014)
A new species of Setostephanolaimus, S. tchesunovi sp. n., is described from bottom sediments collected in the Skagerrak and Gullmarn Fjord off the west coast of Sweden. It is characterised by 1.0–1.3 mm long body, outer labial setae 6.5–8.5 µm long, cephalic setae 9–11 µm long, subcephalic setae 4–6 µm long, transversely-oval amphid, female with monodelphic opisthodelphic reproductive system, male with 6–9 tubular and without alveolar supplements, spicules arcuate and 54–64 µm long, gubernaculum with dorsal apophysis. A tabular compendium and dichotomous identification key to species of the genus Setostephanolaimus are provided.